Firm Level Strategy and Value Creation in Small Businesses: The Nigerian Experience - Adedeji Saidi Adelekan; Ayodele Samuel Majekodunmi; powel maxwell Worimegbe (Gadjah Mada International Journal of Business, 2021)
The issue of firm specific strategies and how they affect organizational performance has engendered a lot of discussions in the extant literature. This creates a need to investigate the extent to which firm level strategy influences value creation in small businesses. Premised on the elements of corporate, business and functional level strategies, this study examines the influence of firm strategy on value creation in a developing economy ie. Nigeria. Employing a survey research design, 689 small business owners and managers were surveyed utilizing questionnaire research instruments. Using PLS-SEM, the study reveals that firm strategy is a driver of value creation in small businesses. The study also shows that corporate level strategy and business level strategy are the most significant drivers of value creation. The results of this study highlight critical concerns and guide small businesses through the value creation process to achieve competitiveness. Small firms should be active in the formulation and implementation of strategies that are based on value creation. More attention should be given to business level strategy, as this is the most significant driver of value creation.